220k views
9 votes
-6(2r + 8) = -10(r - 3)

User Rivo
by
5.8k points

2 Answers

10 votes

Answer:

r=-39

Explanation:

-6(2r + 8)= -10(r-3) solve -6(2r+8)

-12r-48= -10(r-3) solve -10(r-3)

-12r-48= 10r+30

+48 +48

-12r=-10r+78

+10r +10r

-2r=78

-2r/-2=78/-2

r=-39

User Gabrielius
by
4.9k points
1 vote

Hey there!


-6(2r + 8) = -10(r - 3)

-6(2r) - 6(8) = -10(r) - 10(-3)

-12r - 48 = -10r + 30


ADD 10r to BOTH SIDES

-12r - 48 + 10r = -10r + 30 + 10r


SIMPLIFY IT!


-2r - 48 = 30


ADD 48 to BOTH SIDES

-2r - 48 + 48 = 30 + 48


SIMPLIFY IT!


-2r = 78


DIVIDE -2 to BOTH SIDES

-2r/-2 = 78/-2


SIMPLIFY IT!

r = -39


Therefore, your answer is: r = -39


Good luck on your assignment & enjoy day!


~Amphitrite1040:)

User Robin Rieger
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.